Social Media As Support Career Guidance Services - Tresna Fujie Latifah; Agus Supriyanto; Bambang Suprihatin; Shopyan Jepri Kurniawan (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Guidance and counselling teachers need to understand and be skilled in technology, especially understanding and implementing social media in the current era of disruption. Social media as a means of supporting the implementation of career guidance services. This article is to obtain the stages of career guidance with social media as a service support media. The research method uses literature studies to design social media models in career guidance, using national and international journals and scientific articles. Career guidance in schools has the function of introducing, knowing interests, helping make decisions, and adjusting to the world of work. Interactive media in career guidance services is a multimedia-based service. The function of social media for students is to expand social interaction as an unlimited information field and as a means of directed information. Career guidance needs an active role from guidance and counselling teachers for students. The critical part of school career guidance is to establish themselves and realize meaningful career decisions. Guidance and counselling teachers can apply social media as interactive media in school career guidance services.